Historical perspective of women as victims of human rights violations and the Truth and Reconciliation Commission of South Africa (TRC), 1996-1998 - Mbatha, Ntando Phindile Zamashandu (University of the Free State, 2011)
In South Africa, women are in most cases reduced to secondary citizens. This enhances misconceptions that women did not play a significant role during the apartheid era. Even during the apartheid era, the struggle against unjust laws was seen as a man’s job; women were expected to sit at home and raise children. However, this perception is a fallacy. It became clear by the narratives shared during the Truth and Reconciliation Commission of South Africa (TRC) that women played a role; a very important one. Therefore, the history of South Africa is incomplete without the acknowledgement of women’s role. Using the TRC as a case study, this research attempts to illustrate and analyse the role of women in reconstructing the past. It is true that many historians and researchers have written about the TRC; however, the issue of women as victims of human rights violations has been seen as ‘unfinished business’. It is therefore the researcher’s aim to stimulate more research on the subject of women as victims and their role during the apartheid era, as well as their statements and testimonies to the TRC. The purpose of this study is to highlight the role played by women during the struggle against apartheid as it emerged from the testimonies of women – with the majority African women - and to remove the belief that only men played a role in the liberation struggle in South Africa. The researcher focused on the victim hearings of the Human Rights Violations Committee and also the Special Hearings for women that were held during the TRC proceedings. Women became more recognised, especially after the Special Hearings which opened up an understanding by South Africans of the role women played and the human rights violations they endured. Thus, this research will provide some information on a field that has been under-explored, in the hope that this will elicit future research. Particularly, the study aims to highlight the role women played, as well as to remind the nation of what women went through, as their role must not be forgotten and become insignificant after the TRC process came to an end. Three case studies will be looked at, of three women who testified before the TRC. The aim is to obtain their view and perspectives on the whole TRC process; how they experienced it, whether they experienced any form of healing and if, given the chance, to do it again would they be willing to do so. Oral interviews were conducted with these three women. The reader should notice the difference between the ways the three interviews were conducted. This also highlights the fact that the women’s stories are a sensitive issue and should thus be treated accordingly. The qualitative research method was employed, as the study is concerned with the recordings of these victims who experienced violations of human rights during the period 1960-1994, which was the period under investigation by the TRC. Oral history methodology is also employed as the study is about the personal memories and narratives of the victims. In essence, it uncovers not only the verbal articulations, but also the non-verbal clues. The value of oral history in this context is the fact that it gives a voice to the voiceless and in the process giving a platform to women to share their narratives which have in the past been left untold. Additionally, the researcher made use of the traditional methods of historical research. This required consultation with various sources and the collection of all possible information dealing with women and the TRC. The focus was on primary and secondary sources, including special reports, the internet, journals, books and audiovisual material, oral testimonies, as well as personal interviews. The mini-thesis is structured into the following chapters: Chapter one gives a background to the establishment of the Truth and Reconciliation Commission of South Africa, explaining what the purpose of the Commission and what gross violations of human rights entail. A profile of women who testified at the TRC is also provided. Chapter two focuses on the Special Hearings for women held in three regions; the aims of these hearings and how this process made the TRC more gender sensitive. Chapter three highlights what women revealed during the victim hearings and Special Hearings for women. Other victim hearings where women testified were also scrutinised, for example, the Prison Hearings. The three case studies were dealt with in this section. Chapter four focuses on what we now know about human rights violations against women that were revealed by the TRC process. The last chapter provides an evaluation, where the researcher evaluates the whole study, as well as giving pointers for future research. The documents of the TRC are housed in the National Archives and Records Service of South Africa (NARS) in Pretoria. Researchers and the public may gain access to all the video tapes of Human Rights Violations Hearings, as well as the TRC Special Report SABC Programme that is housed in NARS. The translations of all the victim hearings are available on the internet and it is through these translations that the wider public may gain access to the TRC victim hearings. It is important to note that this study is not about the whole process of the TRC. It is known to the researcher that the TRC had three committees; however, for the purpose of this study, only the Human Rights Violations Committee will be discussed, with some background mention of the other Committees. The study covers the period 1996-1998. It is common knowledge that the TRC came into existence in 1995 with the introduction of the Promotion of National Unity and Reconciliation Act No. 34 (the Act); however, it started its activities only in 1996 with the first victim hearings being held in April of that year. Since the TRC had a limited time frame (1960-1994) imposed on it by the Act, the TRC process covered a mere fraction of the apartheid era, dealing with only human rights violations which, as set out by the Act, were: killing, abduction, torture and severe ill-treatment. Therefore, this study was also limited to the time-frame of the TRC. The TRC covered a large number of activities which could not be exhausted. Given the scope of this mini-thesis, only a fraction of the information was used by the researcher which resulted in a careful selection of victim hearings that assisted in emphasising the aim of the study. Therefore, the activities and testimonies examined in this study were by no means the only processes with which the TRC was involved. Though this study focuses on the TRC process and women, this should not be seen as a complete study or the final word on the topic. The aim is not to provide answers, but to stimulate further research on the issue of women and the TRC. There are still unanswered questions concerning the story of women and the TRC in general. This is thus not the whole story; however, it provides a perspective on the above-mentioned topic. Therefore, it is advisable that this study be seen as not the last word on the subject. It is hoped that the study will stimulate further historical investigation into the area as more information is made available. The value of this research is the fact that it is fresh and there is still continuing debate on the subject. The contemporary nature of this study also means that most of the women who came before the TRC are still alive. Consequently, they can be contacted and further interviews and research can be conducted with them.
Dissertation (M.A. (History))--University of the Free State, 2017
Keywords: Women; Truth and Reconciliation Commission; Human rights violations; Special hearings for women